New Players in the Infertility of a Mouse Model of Lysosomal Storage Disease: The Hypothalamus-Pituitary-Gonadal Axis - Piomboni, Paola; Governini, Laura; Gori, Martina; Puggioni, Erica; Costantino-Ceccarini, Elvira; Luddi, Alice (Frontiers in Endocrinology, 2014)
Mammalian spermatogenesis is a complex hormone-dependent developmental program where interactions between different cell types are finely regulated. Mouse models in which any of the sperm maturation steps are perturbed provide major insights into the molecular control of spermatogenesis. The Twitcher mouse is a model for the Krabbe disease, characterized by the deficiency of galactosylceramidase, a lysosomal enzyme that hydrolyzes the terminal galactose from galactosylceramide, a typical component of the myelin membrane. In addition, galactosylceramidase catalyzes the hydrolysis of the terminal galactose from galactosyl-alkyl-acyl-glycerol, precursor of seminolipids, specifically expressed on the membrane of germ cells. Previous data reported by our group demonstrated that glycolipids play an important role in sperm maturation and differentiation. Moreover, we hypothesized that the severe impairment of the Central Nervous System that affects the Twitcher mouse could interfere with the hypothalamus-pituitary-gonadal axis function, contributing to infertility. To highlight this hypothesis we have determined, at molecular level, the potential variation in expression pattern of brain hormones involved in spermatogenesis regulation.